Manufactures Building and Formal Gardens, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1908 - University of Washington Libraries. Special Collections Division (1908)
Caption on image: No. X11. A portion of the Manufacturers Building. Printed on verso: Portland Post Card Co. Seattle, Wash. and Portland, Ore. Official Post Card. Copyrighted 1908. A.Y.P.E. Co. PH Coll 777 PPCC.11 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number